Carburizing composite heat treatment method for low carbon low alloy steel parts and its application
Through the carburizing composite heat treatment method of low-carbon and low-alloy steel parts, the microstructure structure of steel parts is regulated, and the shortcomings in the comprehensive regulation and optimization of the core structure and performance of low-carbon and low-alloy steel parts in the existing technology are solved, and steel is realized The product has high surface hardness and good core toughness, and improves production efficiency and hydrogen resistance.
Patent Information
- Application Number
- CN202211650691.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The prior art has shortcomings in regulating the surface and core tissue performance of low-carbon and low-alloy steel parts, especially in the comprehensive regulation and optimization of the core tissue and performance of the workpiece.
Carburizing composite heat treatment methods for low-carbon and low-alloy steel parts, including isothermal normalization, carburizing treatment, composite quenching treatment and medium-low temperature tempering treatment. Through these steps, the microstructure structure of the steel parts is regulated to make the surface of the steel parts form. The complex phase structure of martensite and nanobainite is formed in the core part and a small amount of carbon-rich residual austenite complex phase structure.
The steel parts have high surface hardness and good core toughness, shorten process time, improve production efficiency, and enhance the resistance to hydrogen-induced delayed fracture, prevent hydrogen embrittlement, and avoid sudden accidents.
Smart Images

Figure CN115852103B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat treatment of low-carbon low-alloy steel parts, and specifically provides a carburizing composite heat treatment method for low-carbon low-alloy steel parts and application thereof. Background Art
[0002] Basic parts such as gears and bearings are often made of low-carbon low-alloy steel and are widely used in aerospace, rail transportation, automotive industry and other industries. They are extremely important transmission parts. With the development of automobiles towards lightweight and high-speed rail towards high speed and heavy load, higher requirements are placed on transmission parts such as gears and bearings. For this reason, the preparation of basic parts such as gears and bearings that are "hard on the surface but tough on the heart" has always been the goal. Heat treatment technology is the key to obtaining basic parts such as gears and bearings that are "hard on the surface but tough on the heart".
[0003] Chinese invention patents CN 113737126 A and CN113737125 A both disclose a vacuum carburizing method for obtaining dispersed fine carbides. Invention patent CN113737126A adds an isothermal treatment below the Ac1 temperature between carburizing and quenching, while invention patent CN113737125 A adds a spheroidizing treatment above the Ac1 temperature between carburizing and quenching. The above technical solutions are used to control the morphology of carbides in the carburized layer and improve the surface properties of parts such as gears. However, the comprehensive control and optimization of the core structure and performance of the workpiece are not considered.
[0004] Chinese invention patent CN 110029272 A discloses a high-toughness bearing structure control method and nano-bainite bearing steel, which performs surface induction quenching on the nano-bainite formed by the first heat treatment, and finally transforms the surface structure into martensite to improve the surface hardness of the bearing. However, the use of surface induction quenching to change the surface structure is not suitable for bearings with sudden and complex surface structures (which may cause "sharp corner effect") and is limited.
[0005] Professor Sir Harry Bhadeshia of Cambridge University and SKF Bearing Company have developed nano-bainite bearings and applied them. After austenitization of high-carbon low-alloy steel, it is isothermally treated for a long time (such as 5 to 14 days) at a lower bainite transformation temperature (150℃~350℃) to obtain a bearing mainly composed of nano-bainite. The surface structure / performance of this kind of bearing is consistent with the core structure / performance, and the long-term isothermal treatment in the bainite isothermal transformation temperature range reduces production efficiency.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first object of the present invention is to provide a carburizing composite heat treatment method for low-carbon low-alloy steel parts.
[0008] The second object of the present invention is to provide a low-carbon low-alloy steel part obtained by the above-mentioned composite heat treatment method.
[0009] The third object of the present invention is to provide the application of the above-mentioned composite heat treatment method or low-carbon low-alloy steel parts in the manufacture of gears or bearings.
[0010] In order to achieve the above object, the present invention adopts the following technical scheme:
[0011] The present invention provides a low-carbon low-alloy steel carburizing composite heat treatment method, the composite heat treatment method comprising the following steps:
[0012] S1: Isothermal normalizing treatment is performed on the steel parts;
[0013] S2: after S1, the steel piece is subjected to carburizing treatment, so that the carbon content in the composition at a certain distance from the surface to the center of the steel piece increases while the carbon content in the composition in the center remains unchanged;
[0014] S3: after S2, the steel part is subjected to a composite quenching treatment, which includes:
[0015] S3-1: heating and heat preservation treatment;
[0016] S3-2: first-stage controlled cooling treatment, cooling the steel part to the first quenching temperature Tq0 after S3-1, so that a proper amount of martensite structure is formed in the core of the steel part without structure transformation on the surface;
[0017] S3-3: first-order isothermal treatment, heating the steel piece to a temperature Tp0 after S3-2 and keeping it at this temperature for a time tp0, so that the carbon atoms in the martensite formed in the core are distributed into the retained austenite without the surface undergoing a structural transformation;
[0018] S3-4: Second-stage slow cooling treatment, cooling the steel part to the second quenching temperature Tq1 after S3-3, so that a proper amount of martensite structure is formed on the surface of the steel part;
[0019] S3-5: Second-order isothermal treatment, after S3-4, the steel piece is heated to a temperature Tp1 and kept at this temperature for a time tp1, so that the carbon atoms in the martensite formed on the surface of the steel piece diffuse into the untransformed austenite and the austenite is transformed into a nano-bainite structure;
[0020] S3-6: Cooling the steel part to room temperature after S3-5;
[0021] And S4: after S3, the steel part is subjected to medium-low temperature tempering treatment.
[0022] The present invention also provides a low-carbon low-alloy steel part obtained by the composite heat treatment method.
[0023] The present invention also provides the application of the composite heat treatment method or the low-carbon low-alloy steel part in manufacturing gears or bearings.
[0024] Compared with the prior art, the technical effects of the present invention are:
[0025] The composite heat treatment method of the present invention utilizes carburizing and composite quenching processes, so that the microstructure of the steel surface is a complex phase structure of martensite and nano bainite (nano bainite ferrite + austenite), and the core is a complex phase structure of martensite and a small amount of carbon-rich residual austenite. The steel surface forms an appropriate amount of martensite before the formation of nano bainite, triggering the nucleation of nano bainite and promoting the growth of nano bainite, thereby shortening the process time and improving production efficiency. The steel obtained by the above technology has the characteristics of high surface hardness and good toughness in the core. The steel microstructure contains austenite and carbide particles, which hinder the diffusion of hydrogen atoms, can improve its ability to resist hydrogen-induced delayed fracture, prevent hydrogen embrittlement, and avoid sudden accidents. The steel with this characteristic is particularly suitable for preparing gears and bearings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The various technical features of the present application and the relationship between them are further explained below with reference to the accompanying drawings. The accompanying drawings are exemplary, and some technical features are not shown in actual proportion. In addition, some drawings may omit technical features that are commonly used in the technical field to which the present application belongs and are not essential for understanding and implementing the present application, or additional technical features that are not essential for understanding and implementing the present application may be shown. In other words, the combination of the various technical features shown in the accompanying drawings is not used to limit the present application. In addition, throughout the present application, the same figure numbers refer to the same content. The specific description of the drawings is as follows:
[0027] Figure 1 This is a microstructure photograph of the steel part of Example 2 taken through an optical microscope after physical and chemical test 3, where B is nano-bainite and Block M / A is block Ma / A island;
[0028] Figure 2 is a microstructure photograph of the steel part of Example 2 taken through an optical microscope after physical and chemical test 4, wherein B is nano-bainite and M is martensite;
[0029] Figure 3 is a microstructure photograph of the steel part of Example 2 taken through an optical microscope after physical and chemical test five, where M is martensite;
[0030] Figure 4 It is the ring structure diagram and anti-seepage coating surface of Example 3;
[0031] Figure 5is a process flow chart of the ring of Example 3 in S3, wherein Ac1 represents the starting transformation temperature of the core component austenite, Ac3 represents the ending transformation temperature of the core component austenite, Ac1' represents the starting transformation temperature of the surface component austenite after carburizing, Ac3' represents the ending transformation temperature of the surface component austenite after carburizing, Ms represents the starting transformation temperature of the core component martensite, Mf represents the ending transformation temperature of the core component martensite, Ms' represents the starting transformation temperature of the surface component martensite after carburizing, and Mf' represents the ending transformation temperature of the surface component martensite after carburizing;
[0032] Figure 6 This is a scanning microstructure photograph of the ring of Example 3 taken by a scanning electron microscope at a distance of 0.3 mm from the surface after heat treatment, wherein B is nano-bainite and M is martensite;
[0033] Figure 7 This is a scanning microstructure photograph of the core of the ring of Example 3 after heat treatment, taken by a scanning electron microscope, wherein M is martensite and A is austenite. DETAILED DESCRIPTION
[0034] Unless otherwise defined, all technical and scientific terms used in this application are the same as those generally understood by those skilled in the art to which this application belongs. If there is any inconsistency, the meaning described in the full text of this application or the meaning derived from the content recorded in the full text of this application shall prevail. In addition, the terms used in this description are only for the purpose of describing the embodiments of the present application and are not intended to limit the present application. Below, the specific implementation methods of the present application are described in detail.
[0035] The low carbon low alloy steel in the present invention refers to a steel with a mass percentage of C element between 0.15% and 0.3%, a sum of the mass percentages of alloy elements such as Mn, Si, Cr, Mo, Ni, V, and Ti not higher than 8%, and the rest being Fe and other inevitable impurities. In a preferred embodiment, the components of the low carbon low alloy steel include, by mass percentage: 0.15% to 0.3% C, 1.2% to 3.5% Mn, 0.8% to 1.7% Si, 0.3% to 2.0% Cr, 0.2% to 0.5% Mo and 0.2% to 1.2% Ni, and at least one of 0.05% to 0.25% V and 0.05% to 0.25% Ti, and the rest being Fe and other inevitable impurities; at the same time, the sum of the contents of Mn, Cr, and Mo is not less than 2.8% and not higher than 4.5%, and the sum of the contents of Mn, Si, Cr, Mo, Ni, V, and Ti is not higher than 8%.
[0036] In the steel part of the present invention, adding 0.15% to 0.3% of C is beneficial to improving the hardenability and hardenability of the steel part and obtaining a martensitic structure with higher strength; by controlling the content of Si, the formation of carbides in the first-order controlled cooling-first-order isothermal-second-order slow cooling-second-order isothermal composite quenching process is avoided, thereby deteriorating the toughness of the steel part; by controlling the contents of Mn, Cr and Mo, the starting transformation temperature of bainite after carburizing can be effectively reduced, which is beneficial to forming a nano-bainite structure in the second-order isothermal process, while improving the hardenability of the material, and is beneficial to obtaining the required martensitic structure and higher strength; adding a certain amount of Ni can improve the impact toughness of the steel part, but the price of Ni is relatively high and needs to be strictly controlled; by adding a certain amount of V and Ti elements, dispersed carbide particles are formed, which is beneficial to refining the grains of the steel part and can also be used as hydrogen traps to avoid the risk of hydrogen embrittlement.
[0037] The low-carbon low-alloy steel carburizing composite heat treatment method provided by the present invention mainly includes four stages: isothermal normalizing treatment in S1, carburizing treatment in S2, composite quenching treatment in S3, and medium-low temperature tempering treatment in S4.
[0038] Isothermal normalizing treatment of S1
[0039] Isothermal normalizing is a heat treatment process in which the steel is heated to austenite and kept warm for a period of time. After the insulation is completed, the steel is cooled to the nose of the S curve and kept isothermally so that the supercooled austenite is transformed within this temperature range to obtain a finer pearlite structure, and then air-cooled.
[0040] In one embodiment, the isothermal normalizing treatment process includes: placing the steel part into a heating furnace that has been heated to T11 and keeping it warm for t11, then controlling cooling to T12, quickly sending the workpiece with a temperature of T12 into a heating furnace that has been heated to T12 and keeping it warm for t12, and finally slowly cooling to room temperature, wherein T11 is 880-1050°C, t11 is 30-240min, T12 is 500-750°C, and t12 is 30-180min.
[0041] In a preferred embodiment, the process of isothermal normalizing treatment comprises the following steps:
[0042] S1-1: Place the steel part in the first heating furnace, heat the steel part to T11 (880-1050°C) at 60-100°C / h, and keep it warm for t11 (30-240min).
[0043] S1-2: Take the steel piece that has completed S1-1 out of the first heating furnace and cool it to T12 (500-750°C). The cooling method is preferably strong wind or spray cooling.
[0044] S1-3: The steel parts that have completed S1-2 are quickly sent into the second heating furnace that has been heated to T12 (500-750°C) and kept warm for t12 (30-180min).
[0045] S1-4: Take the steel parts that have completed S1-4 out of the second heating furnace and slowly cool them to room temperature. The slow cooling method is weak wind cooling or natural air cooling.
[0046] In a preferred embodiment, the structure of the steel part after S1 treatment is ferrite and pearlite.
[0047] It should be noted that the heating rate in S1-1 can be but is not limited to 60℃ / h, 65℃ / h, 70℃ / h, 75℃ / h, 80℃ / h, 85℃ / h, 90℃ / h, 95℃ / h or 100℃ / h; T11 can be but is not limited to 880℃, 900℃, 920℃, 940℃, 960℃, 980℃, 1000℃, 1020℃ or 1050℃; t11 can be but is not limited to 30min, 40min, 50min, 80min, 100min, 130min, 160min, 200min or 240min. In S1-2, T12 may be, but is not limited to, 500° C., 520° C., 540° C., 550° C., 580° C., 600° C., 620° C., 640° C., 650° C., 680° C., 700° C., 720° C., or 750° C. In S1-3, t12 may be, but is not limited to, 30 min, 60 min, 90 min, 120 min, 150 min, or 180 min.
[0048] Carburizing treatment of S2
[0049] Carburizing refers to a chemical heat treatment process in which the steel is heated and kept warm in a carburizing medium to increase the carbon content of the surface of the steel and form a certain carbon concentration gradient from the surface to the core of the steel so that carbon atoms penetrate into the surface. The carburizing treatment method can be protective atmosphere carburizing or pulse carburizing.
[0050] In some embodiments, the carburizing treatment includes:
[0051] S2-1 Apply anti-seepage agent: Apply a layer of anti-seepage agent to the parts of the steel that have completed S1 isothermal normalizing and do not need carburizing treatment.
[0052] S2-2 Carburizing treatment: Place the steel parts that have completed S2-1 into the third heating carburizing furnace which has been heated to T21 (900-960°C) and has a carbon potential of Cp1 (0.1% higher than the carbon content required on the surface of the steel parts after carburizing), and keep warm for t21 (depending on the required carburizing depth). Then lower the heating furnace temperature to T22 (880-920°C), adjust the carbon potential to Cp2 (consistent with the carbon content required on the surface of the steel parts after carburizing), and keep warm for t22 (1 / 4-1 / 2 of t21).
[0053] In a preferred embodiment, Cp1 is preferably 0.6% to 0.9%, t21 is preferably 4 to 12 h, and Cp2 is preferably 0.5% to 0.8%.
[0054] S2-3 Cooling treatment: Cool the steel parts that have completed S2-2 carburizing treatment to room temperature. The cooling method is preferably weak wind or natural air cooling.
[0055] It should be noted that T21 can be, but is not limited to, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, and 960°C; Cp1 can be, but is not limited to, 0.6%, 0.62%, 0.64%, 0.66%, 0.68%, 0.70%, 0.72%, 0.74%, 0.76%, 0.78%, 0.8%, 0.82%, 0.84%, 0.86%, 0.88%, and 0.9%; t21 can be, but is not limited to, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, and 9.5h , 10h, 10.5h, 11h, 11.5h, 12h; T22 can be but not limited to 880℃, 890℃, 900℃, 910℃, 920℃; Cp2 can be but not limited to 0.5%, 0.52%, 0.54%, 0.56%, 0.58%, 0.6%, 0.62%, 0.64%, 0.66%, 0.68%, 0.70%, 0.72%, 0.74%, 0.76%, 0.78%, 0.8%; t22 can be but not limited to 1h, 1.5h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h.
[0056] Composite quenching treatment of S3
[0057] Quenching is a heat treatment method, including continuous cooling quenching and isothermal quenching. Continuous cooling quenching of steel is a heat treatment method in which the steel is heated to a temperature above the critical temperature Ac3 (hypoeutectoid steel) or Ac1 (hypereutectoid steel), kept warm for a period of time to make it fully or partially austenitized, and then rapidly cooled to below Ms (or isothermally near Ms) at a cooling rate greater than the critical cooling rate for martensite (or bainite) transformation. Isothermal quenching of steel is a heat treatment method in which the steel is heated to a temperature above the critical temperature Ac3 (hypoeutectoid steel) or Ac1 (hypereutectoid steel), kept warm for a period of time to make it fully or partially austenitized, and then rapidly cooled to between the bainite start transformation temperature and the bainite end transformation temperature at a cooling rate greater than the critical cooling rate, and isothermally for a period of time for bainite transformation.
[0058] In the present invention, the composite quenching treatment adopts a first-stage controlled cooling treatment-a first-stage isothermal treatment-a second-stage slow cooling treatment-a second-stage isothermal treatment. In the cooling stage of the steel part, the first-stage controlled cooling treatment is implemented, and the cooling time is appropriate, so that the core of the steel part is cooled to a temperature between the martensite start transformation temperature and the martensite transformation end temperature of the steel part core component to form an appropriate amount of martensite structure, while at this time, the surface does not undergo a structural transformation due to carburization to improve the stability of austenite; then the first-stage isothermal treatment is implemented, and the heat preservation time is appropriate, so that the carbon atoms in the martensite formed in the core of the steel part are distributed to the residual austenite, and because the isothermal time is shorter than the incubation period of the surface austenite undergoing isothermal transformation at this temperature , at this time, no structural transformation occurs on the surface of the steel part; then a second-order slow cooling treatment is implemented, and the cooling time is appropriate, so that the steel part is cooled to a temperature between the martensite start transformation temperature and the martensite transformation end temperature of the surface composition after carburizing treatment to form an appropriate amount of martensite structure; then a second-order isothermal treatment is implemented, and the heat preservation time is appropriate, and the carbon atoms in the martensite formed on the surface of the steel part first diffuse into the untransformed austenite, and at the same time, the austenite is transformed into a nano-bainite structure; finally, a cooling treatment is implemented, that is, the steel part is cooled to room temperature, at which time there is basically no structural transformation.
[0059] In order to realize the above-mentioned tissue phase change process, S3 specifically includes the following steps:
[0060] S3-1: Heating and heat preservation treatment.
[0061] S3-2: a first-stage controlled cooling treatment, in which the steel part is cooled to a first quenching temperature Tq0 after S3-1, so that a proper amount of martensite structure is formed in the core of the steel part without structure transformation on the surface.
[0062] S3-3: first-order isothermal treatment, after S3-2, the steel piece is heated to a temperature Tp0 and kept at this temperature for a time tp0, so that the carbon atoms in the martensite formed in the core are distributed into the retained austenite without the surface undergoing a structural transformation.
[0063] S3-4: Second-stage slow cooling treatment, cooling the steel part to the second quenching temperature Tq1 after S3-3, so that a proper amount of martensite structure is formed on the surface of the steel part, the nano-bainite is refined and the S3-5 nano-bainite transformation is promoted, thereby shortening the process time.
[0064] S3-5: Second order isothermal treatment, after S3-4, the steel piece is heated to a temperature Tp1 and kept at this temperature for a time tp1, so that the carbon atoms in the martensite formed on the surface of the steel piece diffuse into the untransformed austenite and the austenite is transformed into a nano-bainite structure.
[0065] S3-6: Cooling the steel part to room temperature after S3-5.
[0066] In a preferred embodiment, the specific method of S3 is preferably as follows:
[0067] S3-1: Place the steel parts that have completed the S2 carburizing treatment into the fourth heating furnace that has been heated to T31 (850-950°C) and keep the temperature for t31 (30-120min).
[0068] T31 may be, but is not limited to, 850°C, 870°C, 880°C, 900°C, 910°C, 920°C, 930°C, 930°C, 950°C; t31 may be, but is not limited to, 30min, 50min, 70min, 90min, 100min, 110min, 120min.
[0069] S3-2: Take out the steel piece that has completed S3-1 from the fourth heating furnace, and cool the steel piece to the first quenching temperature Tq0. The first quenching temperature Tq0 is a temperature between the martensitic transformation start temperature Ms0 and the martensitic transformation end temperature Mf0 of the core component of the steel piece.
[0070] In a preferred embodiment, the first quenching temperature Tq0 is such that fm0 in the following formula is 0.9 to 0.95:
[0071] f m0 =1-exp[α m0 *(Ms0-Tq0)]
[0072] α m0 ={27.2-∑S i *x i -19.8*[1-exp(-1.5*x c0 )]}*10 -3
[0073] ∑S i *x i =0.14*x Mn +0.21x Si +0.11*xCr +0.08*x Ni +0.05*x Mo
[0074] Ms0=489.9-316.7*x C0 -33.3*x Mn -27.8*x Cr -16.7*x Ni -11.1*(x Si +x Mo )
[0075] Mf0=Ms0-150
[0076] In the above formula, X C0 is the mass percentage of carbon in the steel before carburizing, X Mn , X Si , X Cr , X Ni , X Mo They are the mass percentages of manganese, silicon, chromium, nickel and molybdenum in the steel parts respectively.
[0077] In a preferred embodiment, in S3-2, the cooling method is strong wind cooling or spray cooling.
[0078] S3-3: First-order isothermal treatment, the steel parts that have completed S3-2 are placed in a heat treatment chamber that has been heated to Tp0 and kept at this temperature for a time of tp0. The temperature Tp0 is a temperature between the martensite transformation temperature Ms1 of the surface components of the steel parts and the martensite transformation temperature Ms0 of the core components of the steel parts. Ms1 is obtained by the following formula;
[0079] Ms1=489.9-316.7*x C1 -33.3*x Mn -27.8*x Cr -16.7*x Ni -11.1*(x Si +x Mo )
[0080] In the above formula, X C1 It is the mass percentage of carbon in the surface composition of steel after carburizing. C1 The temperature is preferably 0.5% to 0.8%; the temperature Tp0 is preferably 200 to 360°C. Tp0 can be, but is not limited to, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C or 360°C.
[0081] In a preferred embodiment, Ms1 is smaller than Mf0.
[0082] The holding time tp0 is less than the bainite transformation incubation period t corresponding to the surface composition of the steel during the first-order isothermal treatment. b , t b It can be obtained through the MUCG83 software developed by Cambridge University, preferably 8 to 30 hours.
[0083] In a preferred embodiment, the holding time tp0 is 10 min to 120 min. tp0 may be, but is not limited to, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 80 min, 100 min or 120 min.
[0084] In some embodiments, in order to facilitate the actual operation to obtain various data, various data detections can be performed at, for example, 0.3 mm from the surface of the steel part. For example, the martensite start transformation temperature Ms1 of the surface composition of the steel part after carburization, the martensite end transformation temperature Mf1 of the surface composition of the steel part after carburization, the mass percentage of carbon element X in the surface composition of the steel part after carburization, C1 , Tp0 corresponds to the bainite transformation incubation period t during isothermal treatment b All of them are the corresponding test values of the composition at 0.3mm from the surface of the steel part after carburizing, which are used as the corresponding values of the surface composition of the steel part.
[0085] S3-4: Secondary slow cooling treatment, taking the steel piece that has completed S3-3 out of the fifth heating furnace, and cooling the steel piece to the second quenching temperature Tq1; wherein the second quenching temperature Tq1 is a temperature between the martensite start transformation temperature Ms1 and the martensite transformation end temperature Mf1 of the surface component of the steel piece. The cooling method is preferably strong wind cooling or weak wind cooling.
[0086] In a preferred embodiment, Tq1 is such that fm1 in the following formula is 0.1 to 0.35;
[0087] f m1 =1-exp[α m1 *(Ms1-Tq1)]
[0088] α m1 ={27.2-∑S i *x i -19.8*[1-exp(-1.5*x c1 )]}*10 -3
[0089] ∑S i *x i =0.14*x Mn +0.21x Si +0.11*x Cr +0.08*x Ni+0.05*x Mo
[0090] Mf1=Ms1-150
[0091] In a preferred embodiment, Tq1 is 50 to 200° C. Tq1 may be, but is not limited to, 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., 190° C. or 200° C.
[0092] S3-5: Second stage isothermal treatment, the steel parts completed in S3-4 are placed in the sixth heating furnace which has been heated to Tp1 and kept at temperature t p1 , the calculation formula of temperature Tp1 is as follows, where 200<σ γ <280:
[0093]
[0094] T p1 =T r +25
[0095] In a preferred embodiment, the temperature Tp1 is 200°C to 340°C; the holding time t p1 Preferably, it is 8 to 30 hours. Tp1 may be, but is not limited to, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C or 340°C; tp1 may be, but is not limited to, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h or 30h.
[0096] S3-6: Cooling the steel part to room temperature after S3-5;
[0097] In a preferred embodiment, the cooling of S3-6 can be weak wind cooling or natural air cooling.
[0098] Medium and low temperature tempering treatment of S4
[0099] Tempering is a heat treatment method in which the workpiece is heated to a temperature below Ac1 (the starting temperature of pearlite to austenite transformation during heating) after quenching, kept at a certain temperature for a certain period of time, and then cooled to room temperature. Tempering is divided into low-temperature tempering (tempering of the workpiece at 150-250°C), medium-temperature tempering (tempering of the workpiece between 360-500°C) and high-temperature tempering (tempering of the workpiece above 500-650°C).
[0100] The medium-low temperature tempering treatment of S4 includes the following steps: placing the steel part that has completed S3 into a heating furnace that has been heated to T41 (100-360°C) and keeping it warm for a time of t41 (60-240 minutes), then taking it out of the furnace and cooling it to room temperature.
[0101] T41 may be, but is not limited to, 100°C, 150°C, 200°C, 250°C, 300°C or 360°C; t41 may be, but is not limited to, 60 min, 80 min, 100 min, 120 min, 140 min, 160 min, 180 min, 200 min, 220 min, 240 min.
[0102] In a preferred embodiment, the cooling method of S4 can be natural air cooling or strong wind cooling.
[0103] The low-carbon low-alloy steel parts obtained by the composite heat treatment method of the present invention have a surface microstructure of martensite and nano-bainite multiphase structure, and a core microstructure of martensite and a small amount of carbon-rich residual austenite multiphase structure. The steel parts have the characteristics of high surface hardness and good core toughness, and are particularly suitable for the preparation of gears and bearings.
[0104] Embodiment 1:
[0105] The composition and content of low carbon low alloy steel parts are shown in Table 1 below:
[0106] Table 1 Chemical composition and content (mass percentage) of low carbon low alloy steel parts of Example 1
[0107] element C Si Mn Cr Mo Ni V P S content 0.22 1.7 2.0 0.8 0.2 0.6 0.07 0.01 0.005
[0108] According to the chemical composition and content in Table 1, the steel parts are prepared by conventional steelmaking and forging methods. The Ms0 of the steel parts with this composition is 300℃, and the Mf0 is 150℃. The size of the steel parts is 800mm*80mm*30mm (length*width*height);
[0109] Take a number of steel blocks with the size of 30mm (consistent in the length direction of the steel piece)*80mm (consistent in the width direction of the steel piece)*30mm (consistent in the height direction of the steel piece) from the above steel piece, and perform isothermal normalizing treatment on the above test blocks.
[0110] The specific isothermal normalizing process is: put the 30mm*80mm*30mm steel block into a heating furnace at 920℃ and keep it warm for 120min, then cool it to 650℃ by strong wind (cooling rate is about (2℃ / s), then put the steel block into a heating furnace at 650℃ and keep it warm for 150min, finally take it out of the heating furnace and naturally cool it to room temperature.
[0111] Take the steel block that has completed isothermal normalizing as mentioned above to carry out physical and chemical experiment 1.
[0112] The heat treatment method of physical and chemical experiment 1 is as follows: put the steel block that has completed isothermal normalizing into a heating furnace that has been heated to 900℃ and keep it warm for 50 minutes, then cool it to room temperature by air jet, then put the steel block into a heating furnace that has been heated to 250℃ and keep it warm for 12 hours, then take it out and air cool it to room temperature, then put the steel block into a heating furnace that has been heated to 250℃ and keep it warm for 120 minutes, finally take it out from the heating furnace and naturally air cool it to room temperature.
[0113] Take some of the test blocks that have completed isothermal normalizing as mentioned above for physical and chemical experiment 2.
[0114] The heat treatment method of physical and chemical experiment 2 is as follows: the steel block that has completed isothermal normalizing is placed in a heating furnace that has been heated to 900°C, and kept warm for 50 minutes, and then cooled by air jet to 180°C (the corresponding fm0 is 0.92, that is, 92% martensite structure is formed, and the austenite is 8% at this time), and then quickly placed in a heating furnace that has been heated to 280°C and kept warm for 60 minutes, then taken out from the heating furnace and air-cooled to room temperature, and then the test block is placed in a heating furnace that has been heated to 250°C and kept warm for 12 hours, then taken out and air-cooled to room temperature, and then the steel block is placed in a heating furnace that has been heated to 250°C and kept warm for 120 minutes, and finally taken out from the heating furnace and naturally air-cooled to room temperature.
[0115] The conventional mechanical properties of the test block prepared in Example 1 were tested according to the national standard GB / T 228-2002, the impact toughness of the test block prepared in Example 1 was tested according to the national standard GB / T229-1994, and the hardness of the test block prepared in Example 1 was tested according to the national standard GB / T4340-2009 "Vickers Hardness Test for Metallic Materials", as shown in Table 2.
[0116] Table 2 Conventional mechanical properties and impact toughness of different physical and chemical tests in Example 2
[0117]
[0118]
[0119] It can be seen from Table 2 that after the second heat treatment in the chemical test, the material has a good match between strength and toughness, especially better toughness.
[0120] Example 2
[0121] The composition and content of high carbon low alloy steel parts are shown in Table 3 below:
[0122] Table 3 Chemical composition and content (mass percentage) of low carbon low alloy steel parts of Example 2
[0123] element C Si Mn Cr Mo Ni V P S content 0.68 1.7 2.0 0.8 0.2 0.6 0.07 0.01 0.005
[0124] According to the chemical composition and content in Table 3, the steel parts are prepared by conventional steelmaking and forging methods. The Ms0 of the steel parts with this composition is 155℃, and the Mf0 is 5℃. The size of the steel parts is 800mm*80mm*30mm (length*width*height);
[0125] Take a number of steel blocks with the size of 30mm (consistent in the length direction of the steel piece)*80mm (consistent in the width direction of the steel piece)*30mm (consistent in the height direction of the steel piece) from the above steel piece, and perform isothermal normalizing treatment on the above test blocks.
[0126] The specific isothermal normalizing process is: put the 30mm*80mm*30mm steel block into a heating furnace at 920℃ and keep it warm for 120min, then cool it to 650℃ by strong wind (cooling rate is about (2℃ / s), then put the steel block into a heating furnace at 650℃ and keep it warm for 150min, finally take it out of the heating furnace and naturally cool it to room temperature.
[0127] Take the steel block that has completed isothermal normalizing as mentioned above to carry out physical and chemical experiment three.
[0128] The heat treatment method of physical and chemical experiment 3 is as follows: put the steel block that has completed isothermal normalizing into a heating furnace that has been heated to 900℃, keep it warm for 50 minutes, and then cool it to 250℃ (at this time, σ γ is 215MPa, and the bainite transformation incubation period t b The steel block was then quickly placed in a heating furnace that had been heated to 250°C and kept warm for 12 hours, then taken out and air-cooled to room temperature, and then placed in a furnace that had been heated to 250°C and kept warm for 120 minutes, and finally taken out of the heating furnace and naturally air-cooled to room temperature. The tissue photos corresponding to the three samples of the physical and chemical tests were taken using an optical microscope as shown below. Figure 1 As shown in the figure, the organization is nano-bainite and large martensite / Okada multiphase organization. The large martensite / Okada organization is extremely unstable under stress and transforms into a very brittle martensite organization, which deteriorates the material properties, such as contact fatigue. This type of organization should be avoided in the workpiece, especially in basic parts such as gears and bearings.
[0129] Take the above test blocks that have completed isothermal normalizing and carry out physical and chemical experiment 4.
[0130] The heat treatment method of physical and chemical experiment 4 is as follows: put the steel block that has completed isothermal normalizing into a heating furnace that has been heated to 900℃, keep it warm for 50 minutes, and then cool it to 130℃ (the corresponding fm0 is 0.28, that is, 28% martensite structure is formed, and the residual austenite is 72%). Then quickly put the steel block into a furnace that has been heated to 250℃ (at this time, σ γThe steel block was placed in a heating furnace with a pressure of 215 MPa for 12 hours, then removed from the heating furnace and air-cooled to room temperature. The steel block was then placed in a furnace that had been heated to 250°C and kept warm for 120 minutes. Finally, it was removed from the heating furnace and naturally air-cooled to room temperature. The corresponding tissue photos of the four samples of the physical and chemical tests were taken using an optical microscope. Figure 2 As shown, the microstructure is nano-bainite, martensite and fine austenite multiphase structure. Compared with physical and chemical experiment 3, there is no large Martensite / Austenite multiphase structure.
[0131] Take the above test blocks that have completed isothermal normalizing and carry out physical and chemical experiment 5.
[0132] The heat treatment method of physical and chemical experiment 5 is as follows: put the steel block that has completed isothermal normalizing into a heating furnace that has been heated to 900℃, keep it warm for 50 minutes, and cool it to room temperature by spraying air. Then put the steel block into a heating furnace that has been heated to 250℃ and keep it warm for 12 hours. Then take it out of the heating furnace and air cool it to room temperature. Then put the steel block into a furnace that has been heated to 250℃ and keep it warm for 120 minutes. Finally, take it out of the heating furnace and naturally air cool it to room temperature. The tissue photos corresponding to the samples of physical and chemical experiment 5 taken using an optical microscope are shown below. Figure 3 As shown, the structure is unidirectional martensite structure.
[0133] The conventional mechanical properties of the test block prepared in Example 2 were tested according to the national standard GB / T 228-2002, the impact toughness of the test block prepared in Example 2 was tested according to the national standard GB / T229-1994, and the hardness of the test block prepared in Example 2 was tested according to the national standard GB / T4340-2009 "Vickers Hardness Test for Metallic Materials", as shown in Table 4.
[0134] Table 4 Conventional mechanical properties and impact toughness of different physical and chemical tests in Example 2
[0135]
[0136]
[0137] As shown in Table 4, after heat treatment, the hardness of physical and chemical test 4 is slightly lower than that of physical and chemical test 3 and 5, but its toughness is 2 times that of physical and chemical test 3 and more than 4 times that of physical and chemical test 5. The material has a good match of strength and toughness, which is more conducive to improving the damage tolerance, contact fatigue resistance, and anti-stripping properties of basic parts such as gears and bearings. Although physical and chemical tests 3 and 5 have high hardness, they are poor in toughness and brittle, and are prone to spalling and failure during use, shortening the service life of basic parts such as gears and bearings.
[0138] Embodiment 3
[0139] A steel piece with an outer diameter of 25 mm, a wall thickness of 5 mm, and a height of 20 mm is taken from the ring piece with a size of 800 mm*80 mm*30 mm prepared in Example 1. The ring piece is processed by the following four steps S1, S2, S3, and S4.
[0140] S1. Isothermal normalizing treatment, including the following four steps S1-1, S1-2, S1-3, S1-4:
[0141] S1-1: Place the ring into a heating furnace that has been heated to 920°C and keep it warm for 120 minutes.
[0142] S1-2: Take out the ring and cool the steel part to 650°C by air cooling;
[0143] S1-3: Rapidly place the ring into a heating furnace that has been heated to 650°C and keep it warm for 150 minutes.
[0144] S1-4: Take the ring out of the heating furnace and allow it to cool naturally to room temperature.
[0145] S2, carburizing treatment, including the following three steps S2-1, S2-2, S2-3:
[0146] S2-1: Coat the inner surface, upper surface and lower surface of the ring that has completed isothermal normalizing in S1 with a layer of anti-seepage agent (such as Figure 4 );
[0147] S2-2: Place the ring completed in S2-1 into a carburizing furnace heated to 920°C with a carbon potential of 0.76%, and keep it warm for 7 hours; then adjust the temperature of the carburizing furnace to 880°C, the carbon potential to 0.72%, and keep it warm for 2.5 hours.
[0148] S2-3: The ring completed in S2-2 is taken out from the heating carburizing furnace, and the ring is cooled to room temperature by air jet cooling.
[0149] S3 first-stage controlled cooling - first-stage isothermal - second-stage slow cooling - second-stage isothermal composite quenching, including the following S3-1, S3-2, S3-3, S3-4, S3-5, S3-6 (flow chart as shown in Figure 5 ) Six steps:
[0150] S3-1: Place the ring that has completed the S2 carburizing treatment into a heating furnace that has been heated to 900°C and keep it warm for 50 minutes.
[0151] S3-2: Take the ring finished in S3-1 out of the heating furnace and cool the steel to 180°C by air jet cooling.
[0152] S3-3: quickly put the ring completed in S3-2 into a heating furnace that has been heated to 280°C and keep it warm for 60 minutes;
[0153] S3-4: taking the ring finished in S3-3 out of the heating furnace and cooling the steel to 130° C. by air jet cooling;
[0154] S3-5: quickly put the ring completed in S3-4 into a heating furnace that has been heated to 250°C and keep it warm for 12 hours;
[0155] S3-6: Take the ring part completed in S3-5 out of the heating furnace and cool the steel part to room temperature by air jet cooling.
[0156] S4 low temperature tempering treatment includes the following two steps S4-1 and S4-2:
[0157] S4-1: Place the ring that has completed S3 composite quenching into a heating furnace that has been heated to 250°C and keep it warm for 120 minutes.
[0158] S4-4: The rings that have completed S4-1 are taken out of the furnace and naturally air-cooled to room temperature to complete the medium-low temperature tempering treatment.
[0159] The scanned tissue photos of 0.3 mm below the surface and the center of the rings of S1, S2, S3 and S4 are as follows: Figure 6 and Figure 7 It can be seen that the structure 0.3 mm below the surface is a dual-phase structure of martensite and nano-bainite (similar to the structure of physical and chemical experiment 4), while the core is a dual-phase structure of martensite and retained austenite (similar to the structure of physical and chemical experiment 2).
[0160] The carbon content of the ring prepared in Example 3 at a distance of 0.3 mm from the surface was tested by the peeling method, which was about 0.68% (mass percentage, the Ms1 corresponding to this composition was 155°C, and the Mf1 was 5°C); and the hardness of the ring prepared in Example 3 near the surface and the core was tested in accordance with the national standard GB / T4340-2009 "Vickers hardness test for metal materials". The hardness of the surface was 580±10HV, and the hardness of the core was 432±12HV.
[0161] It can be understood that those skilled in the art can combine the features mentioned in one or more embodiments mentioned in the entire application with the features in other embodiments in any appropriate manner to implement the application.
[0162] Note that the above are only preferred embodiments of the present application and the technical principles used. Those skilled in the art will understand that the present application is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the protection scope of the present application. Therefore, although the present application is described in more detail through the above embodiments, the present application is not limited to the above embodiments, and may also include more other equivalent embodiments without departing from the technical concept of the present application, all of which belong to the protection scope of the present application.
Claims
1. A carburizing composite heat treatment method for low-carbon low-alloy steel parts, characterized in that: The following steps are involved: S1: Isothermal normalizing treatment is performed on the steel parts; S2: Carburizing the steel after S1, so that the carbon content of the components at a certain distance from the surface to the center of the steel increases while the carbon content of the components in the center remains unchanged; S3: after S2, the steel part is subjected to a composite quenching treatment, which comprises: S3-1: heating and heat preservation treatment; S3-2: a first-stage controlled cooling treatment, cooling the steel part to a first quenching temperature Tq0 after S3-1, so that a proper amount of martensite structure is formed in the core of the steel part without structure transformation on the surface; The first quenching temperature Tq0 is a temperature between the martensite start transformation temperature Ms0 and the martensite transformation end temperature Mf0 of the core component of the steel part; The first quenching temperature Tq0 makes fm0 in the following formula be 0.9 to 0.95: f m0 =1-exp[α m0 *(Ms0-Tq0)] α m0 ={27.2-∑S i *x i -19.8*[1-exp(-1.5*x c0 )]}*10 -3 ∑S i *x i =0.14*x Mn +0.21x Si +0.11*x Cr +0.08*x Ni +0.05*x Mo Ms0=489.9-316.7*x C0 -33.3*x Mn -27.8*x Cr -16.7*x Ni -11.1*(x Si +x Mo ) Mf0=Ms0-150 In the above formula, X C0 is the mass percentage of carbon in the steel before carburizing, X Mn , X Si , X Cr , X Ni , X Mo are the mass percentages of manganese, silicon, chromium, nickel and molybdenum in the steel parts respectively; S3-3: First-order isothermal treatment, after S3-2, the steel piece is heated to a temperature Tp0 and kept at this temperature for a time t p0 , so that the carbon atoms in the martensite formed in the center are distributed into the retained austenite without the surface undergoing structural transformation; The temperature Tp0 is a temperature between the martensite transformation start temperature Ms1 of the steel surface component and the martensite transformation start temperature Ms0 of the steel core component, and Ms1 is obtained by the following formula: Ms1=489.9-316.7*x C1 -33.3*x Mn -27.8*x Cr -16.7*x Ni -11.1*(x Si +x Mo ) In the above formula, X C1 X is the mass percentage of carbon in the surface composition of the steel after carburizing; C1 0.5% to 0.8%; Ms1 is less than Mf0; The holding time tp0 is less than the bainite transformation incubation period t corresponding to the surface composition of the steel part during the first-order isothermal treatment. b ; S3-4: Second-stage slow cooling treatment, cooling the steel part to a second quenching temperature Tq1 after S3-3, so that a proper amount of martensite structure is formed on the surface of the steel part; The second quenching temperature Tq1 is a temperature between the martensite transformation start temperature Ms1 and the martensite transformation end temperature Mf1 of the surface component of the steel part; The second quenching temperature Tq1 makes fm1 in the following formula be 0.1 to 0.35; f m1 =1-exp[α m1 *(Ms1-Tq1)] α m1 ={27.2-∑S i *x i -19.8*[1-exp(-1.5*x c1 )]}*10 -3 ∑S i *x i =0.14*x Mn +0.21x Si +0.11*x Cr +0.08*x Ni +0.05*x Mo Mf1=Ms1-150 S3-5: Secondary isothermal treatment, after S3-4, the steel piece is heated to a temperature Tp1 and kept at this temperature for a period of time t p1 , so that the carbon atoms in the martensite formed on the surface of the steel diffuse into the untransformed austenite, and at the same time, the austenite is transformed into nano-bainite structure; The calculation formula of temperature Tp1 is as follows, where 200<σ γ <280; T p1 =T r +25 S3-6: Cooling the steel part to room temperature after S3-5; And S4: after S3, the steel part is subjected to medium-low temperature tempering treatment.
2. The carburizing composite heat treatment method according to claim 1, characterized in that: In S3-2, the cooling method is strong wind cooling or spray cooling.
3. The carburizing composite heat treatment method according to claim 1, characterized in that: In S3-3, the temperature Tp0 is a temperature between 200 and 360°C; and the insulation time tp0 is 10 min to 120 min.
4. The carburizing composite heat treatment method according to claim 1, characterized in that: In S3-4, Tq1 is 50-200°C; the cooling method is strong wind cooling or weak wind cooling.
5. The carburizing composite heat treatment method according to claim 1, characterized in that: In S3-5, the temperature Tp1 is 200°C to 340°C; the insulation time t p1 8 to 30 hours.
6. The carburizing composite heat treatment method according to any one of claims 1 to 5, characterized in that: In S3-6, the cooling method is weak wind cooling or natural air cooling; In S3-1, the heating and heat-insulating treatment includes: placing the steel piece that has completed S2 into a heating furnace that has been heated to T31, and keeping it warm for t31, wherein T31 is 850-950°C and t31 is 30-120min.
7. The carburizing composite heat treatment method according to any one of claims 1 to 5, characterized in that: In S1, the isothermal normalizing treatment includes: placing the steel piece into a heating furnace that has been heated to T11 and keeping the temperature for t11, then controlling cooling to T12, quickly sending the workpiece with a temperature of T12 into a heating furnace that has been heated to T12 and keeping the temperature for t12, and finally slowly cooling to room temperature, wherein T11 is 880-1050°C, t11 is 30-240min, T12 is 500-750°C, and t12 is 30-180min; The slow cooling method is weak wind cooling or natural air cooling; The microstructure of the steel after S1 treatment is ferrite and pearlite; In S2, the carburizing treatment is protective atmosphere carburizing or pulse carburizing; In S4, the low temperature tempering treatment includes: placing the steel piece after S3 into a heating furnace that has been heated to T41, and keeping the temperature for a time of t41, and then taking it out of the furnace and cooling it to room temperature; wherein T41 is 100 to 360°C, and t41 is 60 to 240 minutes; In S4, the cooling method is natural air cooling or strong wind cooling.
8. The carburizing composite heat treatment method according to any one of claims 1 to 5, characterized in that: Measured in percentage by mass, the components of the low-carbon low-alloy steel part include: 0.15% to 0.3% C, 1.2% to 3.5% Mn, 0.8% to 1.7% Si, 0.3% to 2.0% Cr, 0.2% to 0.5% Mo and 0.2% to 1.2% Ni, as well as at least one of 0.05% to 0.25% V and 0.05% to 0.25% Ti, and the rest are Fe and other inevitable impurities; at the same time, the sum of the contents of Mn, Cr and Mo is not less than 2.8% and not higher than 4.5%, and the sum of the contents of Mn, Si, Cr, Mo, Ni, V and Ti is not higher than 8%.
9. A low-carbon low-alloy steel part obtained by the carburizing composite heat treatment method according to any one of claims 1 to 8; The microstructure of the surface of the steel piece is a martensite and nano-bainite multiphase structure, and the microstructure of the core of the steel piece is a martensite and a small amount of carbon-rich residual austenite multiphase structure.
10. Use of the carburizing composite heat treatment method according to any one of claims 1 to 8 or the low-carbon low-alloy steel part according to claim 9 in manufacturing gears or bearings.
Citation Information
Patent Citations
Structure adjusting and control method of high-toughness bearing and steel for nano bainite bearing
CN110029272A
Vacuum carburizing method for obtaining dispersed fine carbides
CN113737125A
Vacuum carburizing method for obtaining dispersed fine carbides
CN113737126A
Q&P steel with gradient structure and manufacturing method thereof
CN105463307A
Isothermal quenching process for drill tool steel XGQ25 with high-tenacity complex phase structure distribution
CN105695679A